The Star Menagerie: Personification in Aratus 19–453 and Manilius 1. 263–446 - Vitas, Marko (Literatūra, 2018)
[full article, abstract in English; abstract in Lithuanian]This paper compares Manilius’ use of personification to that of Aratus and his Roman translators. First, I reevaluate the role of personifications in the astronomical texts. I explain the term “personification of the second level” and argue that this type of personification leads to the presentation of the constellations as alive rather than conventional. Further on, it is shown in the paper that Manilius used fewer personifications than Aratus and other comparable texts. I offer two solutions for these results.
Keywords: Aratus, Aratea, Manilius, personification, animals